Retrotransposon and CRISPR/Cas9‑mediated knockout of NOD26 impairs the legume‑rhizobia symbiosis - Frare, Romina Alejandra (2022)
The multifunctional channel NOD26, identified and extensively studied (both biochemically and biophysically) in soybean, is a major protein component of the symbiosome membrane. The water and ammonia transport activities of NOD26 are thought to be important for nodule development, osmotic balance, and ammonia efflux from the symbiosome. However, the widely accepted relevance of NOD26 in nitrogen-fixing symbiosis has never been explored in planta. Recently, we have reported the emergence of NOD26 in the nitrogen-fixing clade of angiosperms via tandem duplication. Here, we characterized the two copies of NOD26 from Medicago truncatula (Medtr8g087710 and Medtr8g087720) in their transport abilities, and at gene expression and genetic levels. Similar to their homologous soybean gene, MtNOD26 genes encode water and ammonia transport activities in heterologous expression systems. By using multiple transcriptional studies (RT-qPCR, transcriptional fusion and RNA-Seq analyses), we found that the expression of MtNOD26 copies is restricted to the nodule and gradually increases from the bacteria-free meristematic region to the nitrogen-fixation zone. Under nitrogen-limiting soil conditions, the homozygous insertional mutant lines of these two MtNOD26 genes had the same aberrant nodulation phenotype and chlorosis. Similar to uninoculated wild-type plants, inoculated mutants were unable to grow in minimal medium without a nitrogen source. Using the CRISPR/Cas9 system, we have edited the orthologous NOD26 genes in Medicago sativa (alfalfa), generating plants with aberrant nodules, chlorosis and impaired grow under nitrogen-limiting conditions. Collectively, our findings suggest functional equivalence between NOD26 copies and underline a crucial role of NOD26 in symbiotic nitrogen fixation.